Inadequate steroid injection after esophageal ESD might cause mural necrosis - Yamashita, Satoshi; Kato, Motohiko; Fujimoto, Ai; Maehata, Tadateru; Sasaki, Motoki; Inoshita, Naoko; Sato, Hiroki; Suzuki, Kenji; Yahagi, Naohisa (Endoscopy International Open, 2019)
Background and study aims Locoregional triamcinolone acetonide (TAC) injection is increasingly used for prevention of stricture after extensive endoscopic submucosal dissection (ESD) for superficial esophageal neoplasia. However, the safety of intramural TAC injection has not been elucidated. The aim of this study was to assess the clinical courses and histopathological changes after TAC injection into the muscle layer in a porcine model.Methods Three pigs were subjected to ESD under general anesthesia. Two artificial 30-mm lesions were created at the oral and anal ends of the esophagus in each pig. TAC was injected into the muscle layer of the artificial oral ulcers (TAC group) and saline was injected into the muscle layer of the artificial anal ulcers (control group). Endoscopic, macroscopic, and histopathological evaluations were performed.Results The artificial ulcers remained open at sacrifice on day 28 post-ESD in the three ulcers injected with TAC. Esophageal wall perforation and abscess spreading to the mediastinum were observed in two of the three ulcers in the TAC group. The abscesses involved the lungs, bronchi, and aortic adventitia. Severe inflammatory cell infiltration in the muscularis propria layer and significant muscularis propria degradation were observed in all three ulcers in the TAC group.Conclusions This study suggests that TAC may cause deep mural damage when it is injected into the muscularis propria. Care should be taken not to inject TAC into the muscle layer when it is used to prevent post-ESD stricture formation.